Metallothermic-synchronous construction of compact dual-two-dimensional MoS2-graphene composites for high-capacity lithium storage. (1st December 2022) - Hao, Xuechun; Zhang, Junfan; Wang, Jing; Zhao, Bo; Qian, Mengmeng; Wang, Ran; Yuan, Qiang; Zhang, Xiaoyan; Huang, Xinwei; Li, Hanlou; Yu, Chuguang; Xie, Jing; et al.
Abstract: Addressing structural degradation of two-dimensional materials is of vast significance for improving their energy storage efficiency and cyclability in alkali metal-ion batteries. Here we propose a one-step metallothermic-synchronous construction strategy of Mo+CS2 =MoS2 +C that can simultaneously generate crystalline MoS2 wrapped by few-layer graphene, forming a compact dual-two-dimensional MoS2 -graphene core-shell structure. XPS analysis reveals that dual-two-dimensional components are connected by chemical bonding of C−S, which promotes electronic and ionic transport and accommodates volumetric change. Notably, electrochemical studies disclose the relationship between storage efficiency and electrode dynamics, as well as cycle stability and volumetric effect of MoS2 -graphene, where the improved electrode dynamics and volumetric efficiency enable high capacity (800 mAh g −1 ) and excellent cyclability (550 mAh g −1 after 500 cycles at 5.0 A g −1 ) for reversible lithium storage. This facile and scalable fabrication strategy makes dual-two-dimensional composite materials potentially viable for the commercialization in high-capacity energy storage. Graphical Abstract: This work establishes a one-step metallothermic-synchronous synthesis strategy (Mo + CS2 = MoS2 + C) to construct a dual-two-dimensional MoS2 -graphene heterostructure, which exhibits high compactness, high conductivity and excellent structural stability, accordingly enabling promising electrochemical performance for lithium storage. The facile and efficient fabrication approach makes such composites suitable for large-scale production and commercialization. ga1 Highlights: A metallothermic synthesis strategy (Mo+CS2 =MoS2 +C) was proposed to construct compact dual-2D MoS2 -graphene heterostructures. MoS2 -graphene featuring chemical bonding of C−S that promotes electronic and ionic transport and accommodates volumetric change during electrochemical reactions. MoS2 -graphene exhibits high-capacity and fast-rate lithium storage, demonstrating the great potential for lithium-ion and other metal-ion batteries.